Dictionary of values - Andres, Tomas Quintin Donato 1942- (Quezon City Giraffe Books, 2000)
A dictionary that consists of terms associated with the different definitions of values. It aims to serve as a reference book for all men and women of all ages, for their lives, studies and courses, especially the social sciences, management and religious sciences at all levels.
This dictionary includes more than 5,000 defined values. It will be a big help to those who are in search of values in their lives, no matter where they are and whoever they are. It is intended for all and it can serve as a reference book for their studies, courses, lives most especially the Social Sciences, Behavioral Sciences, Management Sciences at all levels.
Keywords: Values -- Dictionaries; Social values -- Dictionaries